Diversity and evolution of the extraordinary vocal sacs of casque-headed treefrogs (Anura: Hylidae) - Moura, Pedro Henrique Areco Gomes [UNESP]; Elias-Costa, Agustín J; Nunes, Ivan [UNESP]; Faivovich, Julián (My University, 2021)
Vocal sacs are among the most conspicuous features of anurans and are particularly striking in casque-headed treefrogs (Hylidae: Hylinae: Lophyohylini) with their wide array of morphologies. In this paper, we assessed the anatomy of vocal sacs in representatives of the Lophyohylini, described eight discrete characters and studied their evolution. We inferred that dorsolateral projections of the vocal sacs were already present during the early evolution of the tribe. Subsequently, they reached surprising volumes in some species, whereas in others they were notably reduced. We inferred between nine and 11 independent events of reduction of the size and lateral projections of the vocal sac, showing unprecedented levels of plasticity for the structure. Moreover, these events were strongly correlated with the colonization of phytotelmata as breeding sites, probably due to their confined space which hampers the inflation of large vocal sacs. Finally, we discuss the evolution of paired lateral vocal sacs in different groups of anurans, and the extent to which the paired and dorsally-projecting lobes of most Trachycephalus differ from those of distantly related taxa. Our findings highlight how variation in internal structure affects the shape of the inflated vocal sac and provides a framework applicable across the Anura.
Keywords: comparative anatomy; ecomorphology; Hylinae; optimization; phylogeny; phytotelmata